Karakteristik Budi pekerti kepribadian individu dalam perspektif Al-Qur'an - Ahmad Farid; Imelda; Nisa Afinah (JURNAL ILMIAH RESEARCH STUDENT, 2023)
The Qur'an as a source of universal knowledge for Muslims contains in-depth discussions about every aspect of life, including problems related to human personality. The Qur'an often refers to aspects of human psychology with the term nafs (soul). This proves that the Al-Quran plays a positive role in shaping human personality, apart from being an antidote to mental illness (syifa). Humans were created by Allah SWT different from other creatures, such as angels, jinn, animals and plants. This difference is what gives humans the opportunity to become perfect humans or the worst humans. This year is the time for Muslim scholars to rely on the revelation of the Qur'an to see humans as multidimensional, both physical and mental (spiritual) and not to be haunted by non-Islamic theories that tend to solve problems. The spiritual element in humans has a strong connection with God. It is not enough for humans with their different dimensions to only be considered empirical, but must consider all their dimensions, both physical and mental.